Embryonic origin of the Drosophila brain neuropile. - Younossi-Hartenstein, A.; Nguyen, B.; Shy, D.; Hartenstein, V. (Journal of Comparative Neurology, 2006)
Neurons of the Drosophila larval brain are formed by a stereotyped set of neuroblasts. As differentiation sets in, neuroblast lineages produce axon bundles that initially form a scaffold of unbranched fibers in the center of the brain primordium. Subsequently, axons elaborate interlaced axonal and dendritic arbors, which, together with sheath-like processes formed by glial cells, establish the neuropile compartments of the larval brain. By using markers that visualize differentiating axons and glial cells, we have analyzed the formation of neuropile compartments and their relationship to neuroblast lineages. Neurons of each lineage extend their axons as a cohesive tract ("primary axon bundle"). We generated a map of the primary axon bundles that visualizes the location of the primary lineages in the brain cortex where the axon bundles originate, the trajectory of the axon bundles into the neuropile, and the relationship of these bundles to the early-formed scaffold of neuropile pioneer tracts (Nassif et al. [1998] J. Comp. Neurol. 402:10-31). The map further shows the growth of neuropile compartments at specific locations around the pioneer tracts. Following the time course of glial development reveals that glial processes, which form prominent septa around compartments in the larval brain, appear very late in the embryonic neuropile, clearly after the compartments themselves have crystallized. This suggests that spatial information residing within neurons, rather than glial cells, specifies the location and initial shape of neuropile compartments.